Colgajo pediculado de lengua para el tratamiento de fístula oronasal anterior. Reporte de 3 casos - Gagliardi-Lugo, Antonio (2025)
An oronasal fistula (ONF) is an abnormal communication between the oral cavity and the nose that can be caused by traumatic, post-operative, oncological sequelae and congenital malformations. ONF are usually complicated to treat for multiple local anatomical reasons. Among the various closure options is the pedicled lingual flap (PLF), which can be used to close defects larger than 2 cm, but requires certain additional care during the post operative recovery. Objective: To show, through the report of 3 cases and a review of the literature, the benefits and disadvantages of the PLF surgical technique in cases with oronasal defects greater than 2cm. Case report: 3 male patients, between 17-24 years old, were included. As a consequence of a previous unsuccessful procedure, all of them had anterior palatine fistulas greater than 2 cm, two due to palatoplasty and one as a consequence of a gunshot wound. The patients underwent surgery using the PLF technique. Subsequent follow-ups showed a successful and functional closure. Conclusion: The PLF is a relatively simple and predictable surgical technique, due to the good vascular irrigation provided by the pedicle, resulting in a good option in patients with persistent sequelae of ONF, previously operated on or who do not have an affinity for the use of obturators, the technique provides a safe and higher success rate, as long as the patient understands the difficult commitment of postoperative management and longer recovery time that limits mouth opening, ingestion, hygiene, speech and the need for a second surgical procedure.